Strategic Planning and Management of Human Resources in Educational Institutions - Saiful Bahri (Tarbiyah Departement collaboration with AMCA, 2020)
Strategic planning in educational institutions is the whole process in a mature thought and determination than the things that will be done in the future in order to achieve a predetermined goal. Strategic planning is a dynamic process that must be able to move the entire organization. In general, any organization can undertake strategic planning, but not all organizations need to do so. Management of human resources is a with drawal, selection, development, maintenance, and use of human resources to achieve both goals of individuals and organizations. The function of human resource management as well as general management functions. The purpose of human resource management can be formulated with an effort to leverage the resources both natural resources, capital resources and human resources to achieve goals effectively and efficiently both in terms of productivity or satisfaction in accordance with the values espoused.